A Comparison Study of Wireless Network Security in several Australasian Cities & Suburbs - Nisbet, A; Woodward, A (Springer, 2016)
Wireless network technology has been available for public and private use for almost two decades. The casual approach to security with the early standards and channel selection began to cause issues when the initial security standard, WEP, was discovered to have serious flaws. The closer examination of security and efficiency that followed led to better security protocols, easier setup and better guidelines to ensure efficiency of radio communications. A survey of 5 areas throughout New Zealand was conducted and this is compared with a survey of 5 areas around Perth in Western Australia. The results indicate that whilst improvements continue to be made in security implementations, a small percentage of users do not implement their networks with the recommended settings. Whilst Australian users are slightly better at complying with recommendations, it is clear that some work still needs to be done in the areas of security and efficiency.
Keywords: Wireless; Network; Security; Privacy; Bandwidth